Respuesta :

Answer:

x = 8

Step-by-step explanation:

Solve for x:

-2 x + 16 = 4 (x/4 - 2)

Put each term in x/4 - 2 over the common denominator 4: x/4 - 2 = x/4 - 8/4:

-2 x + 16 = 4 (x/4 - 8/4)

x/4 - 8/4 = (x - 8)/4:

-2 x + 16 = 4 ((x - 8)/4)

(4 (x - 8))/4 = 4/4×(x - 8) = x - 8:

-2 x + 16 = x - 8

Subtract x from both sides:

(-2 x - x) + 16 = (x - x) - 8

-2 x - x = -3 x:

-3 x + 16 = (x - x) - 8

x - x = 0:

-3 x + 16 = -8

Subtract 16 from both sides:

(16 - 16) - 3 x = -16 - 8

16 - 16 = 0:

-3 x = -16 - 8

-16 - 8 = -24:

-3 x = -24

Divide both sides of -3 x = -24 by -3:

(-3 x)/(-3) = (-24)/(-3)

(-3)/(-3) = 1:

x = (-24)/(-3)

The gcd of -24 and -3 is -3, so (-24)/(-3) = (-3×8)/(-3×1) = (-3)/(-3)×8 = 8:

Answer: x = 8